2017
DOI: 10.7717/peerj.3078
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dysregulated genes in rheumatoid arthritis based on bioinformatics analysis

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic auto-inflammatory disorder of joints. The present study aimed to identify the key genes in RA for better understanding the underlying mechanisms of RA.MethodsThe integrated analysis of expression profiling was conducted to identify differentially expressed genes (DEGs) in RA. Moreover, functional annotation, protein–protein interaction (PPI) network and transcription factor (TF) regulatory network construction were applied for exploring the potential biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The role of miRNA regulation in bone diseases has been reported, including osteoporosis and arthritis that are associated with altered bone homeostasis [ 20 , 21 ]. The study of gene associations using the next generation sequencing (NGS) technique and bioinformatics approaches has evolved, providing high-throughput genomic profiling and further understanding and analysis of functional annotations of identified genes and/or miRNAs [ 22 , 23 ]. In this study, we used various bioinformatics tools and databases to assist in identifying potential miRNA–mRNA interactions in osteoblasts of RA population, including miRmap [ 24 ], Gene Expression Omnibus (GEO) [ 25 ], Ingenuity ® Pathway Analysis (IPA) [ 26 ], and Database for Annotation, Visualization and Integrated Discovery (DAVID) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of miRNA regulation in bone diseases has been reported, including osteoporosis and arthritis that are associated with altered bone homeostasis [ 20 , 21 ]. The study of gene associations using the next generation sequencing (NGS) technique and bioinformatics approaches has evolved, providing high-throughput genomic profiling and further understanding and analysis of functional annotations of identified genes and/or miRNAs [ 22 , 23 ]. In this study, we used various bioinformatics tools and databases to assist in identifying potential miRNA–mRNA interactions in osteoblasts of RA population, including miRmap [ 24 ], Gene Expression Omnibus (GEO) [ 25 ], Ingenuity ® Pathway Analysis (IPA) [ 26 ], and Database for Annotation, Visualization and Integrated Discovery (DAVID) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no study that explains the association of "RNA transport" with RA. However, a recent study that analyzed dysregulated genes in RA also found that DEGs were enriched in "RNA transport" among other pathways 53 . This implies that dysregulation of "RNA transport" may play an important role in RA.…”
Section: Results Of Analysis On Ra Datamentioning
confidence: 99%
“…Whole-exome sequencing defined LCK as linked to familial RA and highlighted LCK variation in the T cell receptor (TCR) signaling pathway leading to T cell activation, resulting in T cell differentiation, survival, and effector functions [ 30 ]. Bioinformatics analysis showed that HLA-DRA was dysregulated in RA patients [ 31 , 32 ]. Furthermore, HLA-E was involved in susceptibility to RA and anti-TNF treatment in RA patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%